Effectiveness of Mobile-Assisted Language Learning on EFL Students’ Reading Comprehension - Selfiah Anggraini Pratiwi; Firdaus, Masagus (Universitas Indo Global Mandiri, 2025)
This study investigates the effectiveness and student perceptions of Mobile-Assisted Language Learning (MALL) embedded in English learning applications for English as a Foreign Language (EFL) students. Employing a quantitative quasi-experimental pre-test/post-test design with a correlational component, the study involved 120 upper secondary school students from three public senior high schools in South Sumatra, Indonesia. Two mobile applications, BBC Learning English and English Reading Test, were used over a two-week period. Data were collected using a standardized 25-item multiple-choice reading comprehension test and a validated 20-item perception questionnaire adapted from established reading assessment frameworks. Paired sample t-tests revealed a statistically significant improvement in students’ reading comprehension scores after the intervention (p < 0.05; d = 0.78). Pearson product-moment correlation analysis indicated a positive relationship between students’ perceptions of the assessment features and their reading score gains. Students reported highly positive perceptions, especially in usability and engagement, while feedback mechanisms received slightly lower but still positive ratings. These findings highlight the potential of mobile-based reading comprehension assessments as effective tools for improving reading performance in EFL contexts, provided they are designed with authentic materials, interactive tasks, and timely feedback. Keywords: Mobile-Assisted Language Learning (MALL), reading comprehension, formative assessment